STEM Teacher Candidates’ Preparation for Online Teaching: Promoting Technological and Pedagogical Knowledge - Estaiteyeh, Mohammed; DeCoito, Isha; Takkouch, Mariam (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie, 2024)
Emergency remote teaching during the COVID-19 pandemic has shed light on pedagogical challenges that require the immediate attention of teacher education programs. This paper focuses on teacher candidates’ preparation to teach online in a STEM curriculum and pedagogy course in a teacher education program at a Canadian university. The authors present a two-phase study of two cohorts of teacher candidates enrolled in this course and explore 1) their perceptions of the dynamics and effectiveness of online teaching as a teaching modality, and 2) the impact of the course on their technological and pedagogical skills necessary for online teaching. Quantitative and qualitative data were collected through pre- and post-surveys administered online at the beginning and end of the course. Findings suggest that teacher candidates’ engagement with course content resulted in a notable improvement in their views toward online teaching as a teaching modality, pedagogical approaches, and personal abilities utilizing innovative online teaching strategies. This research emphasizes the necessity for comprehensive training programs that enhance teacher candidates’ technological competencies while simultaneously refining their pedagogical methodologies for online settings. Implications for teacher education research and practice are discussed.